Compound heterozygous variants in NBAS as a cause of atypical osteogenesis imperfecta - Balasubramanian, M (Bone, 2016)
BACKGROUND: Osteogenesis imperfecta (OI), the commonest inherited bone fragility disorder, affects 1 in 15,000 live births resulting in frequent fractures and reduced mobility, with significant impact on quality of life. Early diagnosis is important, as therapeutic advances can lead to improved clinical outcome and patient benefit. REPORT: Whole exome sequencing in patients with OI identified, in two patients with a multi-system phenotype, compound heterozygous variants in NBAS (Neuroblastoma amplified sequence). Patient 1: NBAS c.5741G>A p.(Arg1914His); c.3010C>T p.(Arg1004*) in a 10-year old boy with significant short stature, bone fragility requiring treatment with bisphosphonates, developmental delay and immunodeficiency. Patient 2: NBAS c.5741G>A p.(Arg1914His); c.2032C>T p.(Glu678*) in a 5-year old boy with similar presenting features, bone fragility, mild developmental delay, abnormal liver function tests and immunodeficiency. DISCUSSION: Homozygous missense NBAS variants cause SOPH syndrome (Short stature; Optic atrophy; Pelger-Huet anomaly), the same missense variant was found in our patients on one allele and a nonsense variant in the other allele. Recent literature suggests a multi-system phenotype. In this study, patient fibroblasts have shown reduced collagen expression, compared to control cells and RNAseq studies, in bone cells show that NBAS is expressed in osteoblasts and osteocytes of rodents and primates. These findings provide proof-of-concept that NBAS mutations have mechanistic effects in bone, and that NBAS variants are a novel cause of bone fragility, which is distinguishable from ‘Classical’ OI. CONCLUSIONS: Here we report on variants in NBAS, as a cause of bone fragility in humans, and expand the phenotypic spectrum associated with NBAS. We explore the mechanism underlying NBAS and the striking skeletal phenotype in our patients.